Efficacy and safety of chimeric antigen receptor T-cell (CAR-T) therapy in patients with haematological and solid malignancies: protocol for a systematic review and meta-analysis - Grigor, Emma J M; Fergusson, Dean A; Haggar, Fatima; Kekre, Natasha; Atkins, Harold; Shorr, Risa; Holt, Robert A; Hutton, Brian; Ramsay, Tim; Seftel, Matthew; Jonker, Derek; Daugaard, Mads; et al. (Université d'Ottawa | University of Ottawa, 2017)
Patients with relapsed or refractory malignancies have a poor prognosis. Immunotherapy with chimeric antigen receptor T (CAR-T) cells redirects a patient's immune cells against the tumour antigen. CAR-T cell therapy has demonstrated promise in treating patients with several haematological malignancies, including acute B-cell lymphoblastic leukaemia and B-cell lymphomas. CAR-T cell therapy for patients with other solid tumours is also being tested. Safety is an important consideration in CAR-T cell therapy given the potential for serious adverse events, including death. Previous reviews on CAR-T cell therapy have been limited in scope and methodology. Herein, we present a protocol for a systematic review to identify CAR-T cell interventional studies and examine the safety and efficacy of this therapy in patients with haematology malignancies and solid tumours.
Keywords: car-t; chimeric antigen receptor; leukaemia; lymphoma; malignancy; myeloma; Hematologic Neoplasms; Humans; Immunotherapy; Lymphoma, B-Cell; Neoplasms; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Systematic Reviews as Topic; Antigens, Neoplasm; Receptors, Antigen, T-Cell; T-Lymphocytes